Legal Knowledge Related to Land Registration and Electronic Certification of Land Ownership - Oemar Moechthar; Soelistyowati; Ellyne Dwi Poespasari (VSJ | Veteran Society : Jurnal Pengabdian Masyarakat, 2021)
The dynamics of land in Indonesia have led to various conflicts, one of which is proof of land rights in the form of land rights certificates. The existing conditions, until 2021, it turns out that many rights subjects do not have land rights certificates; they only rely on evidence in the form of old rights, including girik, pipil, kekitir. The proof of the ancient rights proved to be less able to guarantee legal certainty and legal protection than the certificate of land rights stated in the UUPA. In addition, there is Regulation Number 1 of 2021 concerning Electronic Certificates that must be applied. This situation will be a problem that will be discussed related to land registration which is done manually turning into electronic, which is later expected to make it easier for the community to obtain proof of ownership of their land rights. This activity is part of implementing the Tri Dharma of Higher Education, one of which is community service in the form of legal counseling. Through this activity, it is hoped that the community can play an active role in registering proof of land rights for certification and encourage the achievement of "no land ownership without certificates" that the Government can carry out.